Nikifor and Insane Genko. The Insight into the Ekphrastic Polish-Bulgarian Transgressions - Opacka-Walasek, Danuta (Porównania, 2021)
The article discusses the ekphrastic and hypotypotic representations of the characters and the paintings by Epifaniusz Drowniak (Nikifor) and Genko Ivan Genkov (known as “Insane Genko”) that function in the Polish and Bulgarian literary, critical and publicist registers. Both artists’ revelatory bodies of works and traumatic biographies have the legend-creating potential; they were similarly stigmatized, excluded because of their otherness, and as a politically inconvenient Lemko and a dissident. Becoming in their lifetime under systemic conditions of post-war Poland and Bulgaria those countries’ passports to global art, they were subjects of many depreciations. The literary and paraliterary representations of their paintings, personalities (“des idées des tableaux,” “des images des artistes”) are interpreted i.a. in the aspects of exclusion, transgression and performance.